THE EFFECT OF DESTINATION ATTRACTIVENESS AND DESTINATION IMAGE ON REVISIT INTENTION IN LOKON VIEW - Gumolili, Josua; Pandowo, Merinda; Gunawan, Emilia (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
The rapid development of tourist destinations has significantly influenced the city of Tomohon, particularly in the Woloan sub-district, which is now experiencing considerable growth and increased competitiveness. This study aims to analyze the effect of Destination Attractiveness and Destination Image on Revisit Intention in Lokon View, located on Jl. Nimawanua, Woloan Satu Village, West Tomohon District, Tomohon City, North Sulawesi. The survey, conducted through questionnaires, included a sample of 100 respondents from Millennials Generation who have visited Lokon View. Data were analyzed using SPSS 25. The results revealed that Destination Attractiveness (Attraction, Accessibility, and Ancillary Services) and Destination Image (Cognitive Image, Unique Image, and Affective Image) significantly influence Revisit Intention in Lokon View. To enhance revisit intention at Lokon View, focus on improving destination attractiveness by enhancing attractions, accessibility, and ancillary services. Additionally, strengthen the destination image by promoting its cognitive, unique, and affective qualities through targeted marketing and maintaining high service standards.   Keywords: Destination Attractiveness, Destination Image, Revisit Intention